2007
DOI: 10.1063/1.2767535
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic vortex filament flows

Abstract: We exhibit a variational approach to study the magnetic flow associated with a Killing magnetic field in dimension 3. In this context, the solutions of the Lorentz force equation are viewed as Kirchhoff elastic rods and conversely. This provides an amazing connection between two apparently unrelated physical models and, in particular, it ties the classical elastic theory with the Hall effect. Then, these magnetic flows can be regarded as vortex filament flows within the localized induction approximation. The H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
73
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(83 citation statements)
references
References 26 publications
0
73
0
3
Order By: Relevance
“…Studying Killing magnetic curves in 3-dimensional space forms, Barros and Romero showed in [10] that these curves are centerlines of Kirchhoff elastic rods. Further on, Barros et al in [9] showed that these curves are solitons of the localized induction equation (LIE). A more global and geometric view on the connection between solitons of LIE and magnetic curves are provided in [29].…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Studying Killing magnetic curves in 3-dimensional space forms, Barros and Romero showed in [10] that these curves are centerlines of Kirchhoff elastic rods. Further on, Barros et al in [9] showed that these curves are solitons of the localized induction equation (LIE). A more global and geometric view on the connection between solitons of LIE and magnetic curves are provided in [29].…”
Section: Introductionmentioning
confidence: 97%
“…Let us denote the corresponding divergence-free vector field of F by V and the 1-form that is metrically dual to V by ω. If V is a unitary vector field, then (φ ,V, ω) is an almost contact structure on M compatible with the metric g. Hence, an oriented Riemannian 3-manifold (M, g) together with a magnetic field F whose corresponding divergence-free vector field has unit length is regarded as an almost contact metric manifold with closed fundamental 2-form, see [9].…”
Section: Introductionmentioning
confidence: 99%
“…It is clear that, any Killing vector …eld on (M n ; g) is divergence-free. In particular, if n = 3, then every Killing vector …eld de…nes a magnetic …eld that will be called a Killing magnetic …eld [1].…”
Section: Preliminariesmentioning
confidence: 99%
“…If the charged particle moves parallel to magnetic field, the Lorentzian force acting on the particle is zero. When the two vectors (velocity and the magnetic field) are perpendicular to each other, the Lorentz force is maximum (for details, see [4,2,3,6,7,9,8]). …”
Section: Introductionmentioning
confidence: 99%
“…It is clear that any Killing vector field on (M n , g) is divergencefree. In particular, if n = 3, then every Killing vector field defines a magnetic field that will be called a Killing magnetic field (for details, see [2]). …”
Section: Introductionmentioning
confidence: 99%